Violence against Teachers in Jordanian Schools - Alzyoud, Mohammad Sayel; Al-Ali, Ali Salem; Tareef, Atif O. Bin (European Scientific Journal, ESJ, 2016)
This aim of this study is to examine the reasons for violence against teachers in Jordan from the perspective of high school students. The study followed a qualitative research approach by interviewing (50) students from grade twelve. Students were recruited in this study via the convenience sampling approach. The study revealed that teachers, school administration, school environment, media, and family conditions, were the major causes of student’s violence against teachers. Teachers who experienced violence from students are the cause of this violence due to their actions and practices. Teachers are often exhausted, dispassionate, and overloaded with teaching and administrative duties. As a result, these duties sometimes hinder them not to communicate with students nicely or help students in solving their problems. Other times, students are violent against teachers because some teachers have low academic and educational performances. They are unable to offer counselling and psychological support to students from certain backgrounds. Subsequently, some students lack proper morals and discipline. School administrators are to be held responsible for the violence against teachers because they are unable to meet the students’ needs.